Nominal Number Marking in Wolane - Meyer, Ronny (Aethiopica, 2010)
Countable common nouns in the East Gurage language Wolane are usually unmarked for number and belong to one of three noun classes based on the inherent gender feature of the nouns. First, it will be argued that morphological plural marking indicates plurality and specificity. Second, it will be shown that the interaction between the three noun classes and definiteness has various pragmatic effects. Finally, the findings for Wolane are compared with related East Gurage languages.